Kecernaan In Vitro Komponen Serat Ransum Ternak Sapi yang Menggunakan Kulit Buah Jagung Amoniasi - Andayani, Jul (Fakultas Peternakan Universitas Jambi, 2009)
An experiment was conducted to evaluate in vitro digestibility of fiber components of the cattle ration containing ammoniated corn husk. Parameters measured in the present experiment were Dry Matter (DM), Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF) in vitro digestibilities. This study was assigned into completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were ; T0 = 70% Forage (100% grass + 0% ammoniated Corn husk) + 30 % Concentrate, T1 = 70% Forage (75 % grass + 25% ammoniated Corn husk) + 30 % Concentrate, T2 = 70% Forage (50% grass + 50% ammoniated Corn husk) + 30 % Concentrate, T3 = 70% Forage (25% grass + 75% ammoniated Corn husk) + 30 % Concentrate, T4 = 70% Forage (0% grass + 100% ammoniated Corn husk) + 30 % Concentrate. Results of this study showed that the treatments were significantly (P<0,05) influence of dry matter, NDF and ADF digestibilities. Increasing percentage of corn husk ammoniation in the ration increased in vitro digestibility. It is concluded that ammoniation with urea to corn husk could increase digestibility and the ammoniated corn husk ammoniation may substitude forage for cattle ration.